Tailing pond stability monitoring method based on multi-sensor fusion and improved splitting method - DING SHOUQIANG; YAO LEIBO; HAI YANG (2024)
The invention relates to a multi-sensor fusion-based tailing pond stability monitoring method based on an improved splitting method. Comprising the following steps: monitoring the external displacement and the internal displacement of a dam body in real time, monitoring the stability of the tailings pond by combining an analysis result of the stability of the dam body by an improved slice method, intensively analyzing and processing monitoring data, and carrying out early warning on the stability of the tailings pond according to a data processing result. The method solves the problems that in existing tailing dam slope stability analysis, a large amount of basic data needs to be manually measured during monitoring each time, and then a computer is used for calculation to obtain a result; the elevation of a single soil strip, the height of a water-containing soil strip and the height of a water-free soil strip are not real-time data and are not distinguished; the technical problem that the landslide mass is n